The Relationship of Level of Digital Literation Program Implementation at Senior High School with the Level of Political Participation of Beginner Voters in Malang Raya - Nyimas Nadya Izana; Dewi Puspita Rahayu (Institute of Research and Community Service, University of Brawijaya)
In this digital era, social media has become one of the tools of political communication channels. Like what happened at the 2019 general election, political campaigns also used social media. The activities aim to boost the voice especially from the younger generation who are the biggest internet users in Indonesia. Unfortunately, political campaign activities were also accompanied by increased hoaxes before and after the voting day. The emergence of the phenomenon of the spread of hoaxes is actually due to the low digital literacy in the community. Kemendikbud has launched a digital literacy program since 2016 to address this problem, especially for school students. This research aims to look at the relationship of level of digital literation program implementation at senior high school with the level of political participation of young voters in Malang Raya. The research method in this research was quantitative inferential with correlation test. The population in this research were high school students who have the right to vote in the 2019 general election in the Malang Raya area. The number of samples in this research were 503 respondents. The sampling technique used multistage random sampling. The results showed that there was a relationship between the level of digital literation program implementation at senior high school with the level of political participation of young voters in Malang Raya. Categories for each major variable were also classified as high, namely 68,8% in the variable level of digital literacy implementation, and 64,6% in the variable level of political participation.